Emerging East Asian Banking Systems Ten Years after the 1997/98 Crisis - Charles Adams (Asian Development Bank (ADB), 2008)
This paper looks at the development of the banking sector in emerging East Asia in the 10 years since the financial crisis of 1997/98. It suggests that the health of banking sectors in the region has improved substantially, with key changes including increased foreign ownership, movement into new business lines, greater transparency, and shifts toward household and real estate lending. In addition, supervisory and regulatory systems have been upgraded and have become more forward looking and risk based. However, it notes that major credit rating agencies continue to maintain relatively low ratings for many banks in the region, bank share prices have generally underperformed the market, and significant differences persist in the health of the region's banking systems. In addition, bank lending to private business has been weak across much of the region. Restructuring and reform are ongoing processes and will need to continue not only where further rehabilitation from the effects of the 1997/98 crisis is still required, but in other economies as well.
hdl:11540/1767
Keywords: G21; G24; G28; G32; 330; Financial crisis; restructuring and reform; credit rating; Basel core principles